Muscle morphology and performance in sprinting, jumping and throwing - Methenitis, S.; Zaras, N.; Stasinaki, A.; Spengos, K.; Papadopoulos, C.; Karampatsos, G.; Krekoukia, M.; Krase, A.; Kavouras, S.; Georgiadis, G.; Manta, P.; Terzis, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Sprinting, throwing and jumping are three commonly used human explosive activities (Newton & Kraemer 1994). Performance in such activities relies upon a wide range of muscles` morphological factors (Cormie et al. 2011). Indeed, significant correlations exist between muscle morphology and performance in these activities. However, the impact of each one of these parameters on sprinting, throwing and jumping is not clear. The purpose of the present study was to identify the impact of selected muscle morphological parameters on sprinting, throwing and jumping performance in novice participants. Methods: Sixty eight novice males performed in random series the following tests: 60m sprint, countermovement and squat jumps, squat underhand and one-arm standing throws. Body composition was evaluated via dual x-ray absorptiometry. Vastus lateralis (VL) thickness (VLT), pennation angles (VLPA) and fascicle lengths (VLFL) were determined with ultrasonography. Thigh muscles cross sectional area (TMCSA) was estimated with skinfold thickness. VL`s fiber type composition was histochemically determined in muscle samples (n=37). Results: Pearson`s r coefficients revealed low to moderate correlations between performance and morphological factors (r : 0.246 - 0.783, p<0.05). Canonical correlation analysis revealed higher correlations between the combination of selected morphological factors and sprinting (rc = 0.650, p = 0.03), throwing (rc =0.782, p = 0.006) and jumping performance (rc < 0.856, p = 0.000). Cross loadings revealed that the order of significance for the muscle morphological factors in sprinting was: lower body lean mass (LBLM; 0.499), VLPA (0.476), TMCSA (0.406), VLT and VLFL (0.386 and -0.387) and % CSA of Type IIx fibers (-0.354), for throwing: LLBM (0.750), body mass index (BMI; 0.721), TMCSA (0.670), VLT (0.511), type IIa % CSA (0.459) and VLFL (0.384), and for jumping: LLBM (0.800), TMCSA (0.534), BMI (0.512), type IIa % CSA (0.439), VLT (0.401) and VLFL (0.392). Discussion: It appears that performance in sprinting, throwing and jumping depends primarily on lower body lean mass and secondary to VL`s architecture characteristics and fiber type composition.